How psychosocial group climate and personality affects teacher burnout. - Espinoza Díaz, Ivette Margarita; Espinoza Díaz, Ivette Margarita; Tous-Pallarès, Jordi; Vigil-Colet, Andrés (Anales de Psicología / Annals of Psychology, 2015)
The present study evaluates how psychosocial group climate and personality affects burnout syndrome (BS) in teachers of infant, primary and secondary education. To do so questionnaires were administered to evaluate psychosocial climate, personality and burnout in a sample of 386 teachers. The study analyzes the relation between these variables and the extent to which the variables of climate and personality allow a predictive model of burnout to be established by means of multiple regression analysis. The results showed that both psychosocial climate (particularly the degree of disorganization) and personality (particularly emotional stability) influence burnout and, although climate factors seem to be better predictors of BS, the use of personality measurements increases the predictive capacity of the syndrome. Therefore, the joint use of these types of predictor increases our ability to establish models that can prevent BS in teaching environments